Haiti School Finance : SABER Country Report 2017 - Mejía, Carlos; Hruskovec, Katherina (World Bank, Washington, DC, 2018)
School finance is an essential component of every education system, but comprehensive guidance on what matters in school finance systems is lacking. SABER-School Finance meets this need with a framework that has dual purposes: to create a knowledge base and to evaluate the quality of school finance systems. First, SABER-School Finance maps systems by collecting comprehensive and standard data in five core areas to describe the policies, official processes, funding mechanisms, and other formal guidelines that influence school finance systems. These data provide context for the assessment of school finance systems, allow countries to learn from systems with similar characteristics, and facilitate future study by other researchers to examine what matters in school finance. The project also enables systems to measure progress toward meeting essential school finance policy goals and gives policy guidance on how best to improve the system. The SABER-School Finance analysis identifies strengths, which can serve as examples to other school finance systems, and weaknesses, or areas to target for reform or additional in-depth research. SABER-School Finance’s data and analyses of the management of educational resources are useful to education policy-makers, researchers, and stakeholders (including World Bank operations staff). In this paper, we discuss the main characteristics of school finance systems, present the evidence supporting the choice of school finance policy goals, and explain how the SABER-School Finance framework provides guidance on what matters most in school finance.